Employee Performance in Islamic Banking:The Roles of Integrity, Competence, and Work Environment (A Study at Bank Syariah Indonesia in Malang Raya, Jawa Timur) - Bambang Ragil; Ernani Hadiyati; Endang Suswati; Sugeng Mulyono (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study aims to examine the effects of integrity, competence, and work environment on employee performance at Bank Syariah Indonesia (BSI) in the Malang Raya area, with work motivation and organizational commitment as mediating variables. The study employed a quantitative, explanatory design. Data were collected from 90 BSI employees through a questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that integrity (β = 0.173; p = 0.027), competence (β = 0.158; p = 0.043), and work environment (β = 0.189; p = 0.013) have positive and significant effects on employee performance. In addition, work motivation (β = 0.336; p < 0.001) and organizational commitment (β = 0.358; p < 0.001) also significantly influence employee performance. Mediation analysis shows that work motivation and organizational commitment act as significant partial mediators, with indirect effect coefficients ranging from 0.090 to 0.117. The coefficient of determination indicates that the proposed model explains 70.3% of the variance in employee performance (R² = 0.703). This study contributes theoretically by developing a dual-mediation employee performance model in the context of Islamic banking and provides practical implications for human resource management at Bank Syariah Indonesia.